The Gospel of Mark - Barclay, William; (1907-1978) (Scotland, 1969)
The Daily Study Bible aims to make the results of modern scholarship available to the general reader in a form that is free from theological, and technical terms, yet precise and full of meaning. Thus the teaching of the New Testament books should, it is hoped, be made more definitely relevant to life and work today. This may be summed up in the words of Richard of Chichester's famous prayer that we may be enabled to know Jesus Christ more clearly, to love Him more dearly, and to follow Him more nearly
Keywords: Bible -- Mark -- Commentaries